1998
DOI: 10.1016/s0168-6496(98)00008-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen oxides and denitrification by Pseudomonas stutzeri on acetotrophic methanogenesis by Methanosarcina mazei

Abstract: Nitrate and its reduced forms produced during denitrification, nitrite and nitrous oxide, were studied for their influence on methane production from acetate by Methanosarcina mazei. While 0.18 mM nitrite and 0.8% nitrous oxide in the gas phase completely suppressed methane production, 71.4 mM nitrate resulted in only 83.3% inhibition. Co-culture experiments showed that M. mazei growing with 15 mM nitrate produced methane from acetate until the denitrifying bacterium Pseudomonas stutzeri was inoculated and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 13 publications
6
21
0
Order By: Relevance
“…This may be due to the competition for nitrate by denitrification by the presence of non-Poly-P denitrifiers. Also denitrifying phosphorus bacteria can use organic substrate directly for growth and nitrate as electron acceptor instead of PO 4 -P. This result agreed with the results obtained by Clarens et al [30], in which they reported that acetate decreased the P uptake and increased the denitrification. However, Ng et al [25] found that a net phosphorus uptake still occurred, which seemed to suggest that the influence of anoxic acetate was not very significant and high COD concentrations decreased the P uptake rates.…”
Section: Effect Of Cod On the Fate Of Po 4 -P Concentrations In Anoxisupporting
confidence: 92%
See 1 more Smart Citation
“…This may be due to the competition for nitrate by denitrification by the presence of non-Poly-P denitrifiers. Also denitrifying phosphorus bacteria can use organic substrate directly for growth and nitrate as electron acceptor instead of PO 4 -P. This result agreed with the results obtained by Clarens et al [30], in which they reported that acetate decreased the P uptake and increased the denitrification. However, Ng et al [25] found that a net phosphorus uptake still occurred, which seemed to suggest that the influence of anoxic acetate was not very significant and high COD concentrations decreased the P uptake rates.…”
Section: Effect Of Cod On the Fate Of Po 4 -P Concentrations In Anoxisupporting
confidence: 92%
“…The feasibility of denitrification in an anaerobic digester has been established to be strongly dependent on the COD/NO 3 -N ratio and the nature of the carbon source [27]. Attempts to carry out denitrification and methane production in a completely mixed reactor have not proved very effective because nitrogen oxides are known to inhibit the methanogenic activity of bacteria [28][29][30]. The biofilter reactor system developed by Akunna et al [31] exhibits a denitrification activity at the bottom and methane production in the upper part, where NO 3 -N had been totally removed.…”
Section: Introductionmentioning
confidence: 99%
“…Following the apparent suppression of SRB activity by nitrite at 50 ppm, effluent acetate levels decreased and effluent propionate and butyrate concentrations were reduced to non-detectable levels [16]. There was no indication, in this study, of inhibition of the syntrophic or methanogenic populations by nitrite, but toxic effects of nitrous oxides have been reported by other authors [2,8,9,17,19]. Kluber and Conrad [8] found that the addition of 5 mM (230 mg L À1 ) nitrite in batch tests on anoxic rice field soil resulted in complete inhibition of methanogenesis with concurrent elevated levels of acetate and propionate, for at least 24 days.…”
Section: Introductionsupporting
confidence: 39%
“…Several investigations have already been reported, which have covered the activity and the behaviour of the microbial communities in anaerobic biogas reactors running on various kind of substrates (Petersen and Ahring 1991;Hedrick et al 1992;Angelidaki and Ahring 1993;Raskin et al 1995;Ahring 1995;Chanakya et al 1997;Clarens et al 1998;Vavilin et al 1998;Oude Elferink et al 1998;Hansen et al 1999). In the following sections of this paper, the roles of acetotrophic and hydrogenotrophic methanogens during anaerobic conversion of particulate biomass to methane will be discussed, respectively, in view of the works recently published in literature.…”
Section: Theory Of the Anaerobic Bacterial Food Chainmentioning
confidence: 99%